KONSTRUKSI STRATEGI GURU DALAM PEMANFAATAN TEKNOLOGI PENDIDIKAN UNTUK MENINGKATKAN KETERLIBATAN BELAJAR SISWA SEKOLAH DASAR: PENDEKATAN GROUNDED THEORY - Suci Mega Dian Sari (http://jurnal.untirta.ac.id/index.php/JTPPm, 2026)
The rapid development of educational technology has transformed learning practices in elementary schools. However, the successful integration of technology is determined not only by the availability of digital tools but also by teachers’ ability to develop effective instructional strategies. This study aims to explore the process through which teachers construct strategies for utilizing educational technology to enhance students’ learning engagement in elementary schools. A qualitative approach employing a Grounded Theory design was adopted. Data were collected through in-depth interviews, observations, and document analysis involving 10–15 elementary school teachers who actively use educational technology. Data analysis was conducted through open coding, axial coding, and selective coding using NVivo 14 software. The findings revealed four major themes: awareness of digital transformation, adaptation of technology-based instructional strategies, negotiation of technological challenges, and students’ learning engagement as an outcome of meaningful digital learning. The study generated a substantive theory of teachers’ adaptive strategy construction in educational technology integration. Practically, the findings provide insights for strengthening teachers’ digital and pedagogical competencies to support more engaging and effective learning environments